Spatiotemporal variations and dynamic mechanisms of cross-shelf heat transport in the East China Sea - Qin, Weifu; Ding, Ruibin; Xuan, Jiliang; Zhou, Feng (Frontiers in Marine Science, 2025)
Cross-shelf heat transport (CSHT) is a key component of the heat budget in the East China Sea. However, long-term observational evidence and a dynamic understanding of its complex spatiotemporal variations remain unclear. This study quantifies CSHT along the 200 m isobath using long-term data derived from satellite and in situ observations, and systematically analyzes its spatiotemporal variations and dynamic mechanisms. During 1993-2022, the net CSHT was 0.10 ± 0.08 PW, with on-shelf and off-shelf components of 0.70 ± 0.12 PW and -0.59 ± 0.08 PW, respectively. CSHT exhibits a dominant seasonal variation, with distinct phase differences between the net value and bidirectional components: the net value peaks in autumn and reaches its minimum in spring, whereas the bidirectional components are strongest in summer and weakest in winter. Depth-integrated results reveal unidirectional dominance in most shelf regions (on-shelf/off-shelf channels contain minimal reverse components). Among them, the northeastern Taiwan shelf, as the strongest on-shelf/off-shelf channel for CSHT, dominates the bidirectional components’ summer-strong/winter-weak pattern, whereas the southwestern Kyushu shelf primarily contributes to the net value’s autumn-strong/spring-weak characteristic. Along-isobath integration shows balanced bidirectional components above 150 m, whereas on-shelf transport dominates below. Dynamical mechanisms indicate that geostrophic transport dominates CSHT, except for bottom Ekman transport in the central shelf. In terms of temporal variations, northeastern Taiwan is mostly active due to geostrophic currents’ variability. Empirical Orthogonal Function analysis further confirms that variations off northeastern Taiwan manifest as an on-shelf/off-shelf dipole structure throughout the entire water column. These results provide new physical insights into heat regulation in the East China Sea.